Perceived Organisational Support Towards Psychological Capital and Organisational Thriving in Lithuania - Savickaite-Kazlauske, Evelina; Bendaraviciene, Rita (International Journal of Applied Research in Management and Economics, 2024)
This study examines the interconnectedness of positive organisational resources at three levels through a cross-sectional analysis of 408 participants from various organisations in Lithuania. It investigates the relationships between Perceived Organisational Support for Strength Use (POSSU) and Deficit Correction (POSDC), Strength Use (SUB) and Deficit Correction Behaviour (DCB) with both individual and collective Psychological Capital (PsyCap) and Organisational Thriving. Findings indicate moderate correlations between POSSU and SUB with both types of PsyCap, which are more robust than those with POSDC and DCB. Significant correlations between POSSU, POSDC, and Organisational Thriving suggest that supportive practices enhance overall perceived thriving. These results imply that managers should create environments encouraging employees to use their strengths for greater positive psychological resources. Despite limitations in design, this study contributes to Positive Organisational Scholarship and Positive Organisational Behaviour by addressing gaps in the links between positive psychological resources at individual, collective, and organisational levels. Future research could use longitudinal or experimental studies to expand these findings and address noted limitations.